Nine receptors and binding proteins, four drugs, and one woman: Historical and personal perspectives - Novick, Daniela (Frontiers in Drug Discovery, 2022)
In the era of bioinformatics and high-throughput techniques, it is tempting to forget the advantage of an old yet efficient and straightforward technique, ligand affinity chromatography, in the search for unknown proteins. This type of separation is based on an interaction between the target analyte potentially present in a crude mixture of proteins and a ligand coupled covalently to a resin. This process allows thousands-fold purification in a single step, which is crucial when using an extremely rich source of naturally occurring proteins such as human urine or plasma. Before the completion of The Genome Project, this method facilitated the rapid and reliable cloning of the corresponding gene based on the partial amino acid sequence of the isolated protein. Upon completion of this project, a partial protein sequence was enough to retrieve its complete mRNA and, hence, its complete protein sequence. Ligand affinity chromatography is indispensable for the isolation of both expected and unexpected binding proteins found by serendipity. My approach of combining a rich source of human proteins (1,000-fold concentrated human urine) together with this highly specific isolation method yielded proteins from both groups. The expected proteins included the two receptors for TNF (TBPI and TBPII), type I and type II interferon receptors (IFNα/βR, IFN-γR), and IL-6 and LDL receptors. The unexpected group of proteins included IL-18 binding protein (IL-18BP), IL-32 binding protein (Proteinase 3), and heparanase binding protein, the resistin. The discovery of the type I IFN receptor was a “eureka” moment in my life since it put an end to a 35-year worldwide search for this receptor. Using chemical purification methods, the TBPII might have never been discovered. Years later, TBPII was translated into the blockbuster drug Enbrel® to treat mainly rheumatoid arthritis. IFN-beta was translated into the blockbuster drug Rebif® to treat the autoimmune disease multiple sclerosis. IL-18BP translated into the drug Tadekinig alfa™ and is in a phase III clinical study for inflammatory and autoimmune pathologies. It has saved the lives of children born with mutations (NLRC4, XIAP) and is an example of personalized medicine. COVID-19 and CAR-T cytokine storms are the recent targets of IL-18BP.